2019
DOI: 10.1249/mss.0000000000002207
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Deprivation: Cytokine and Neuroendocrine Effects on Perception of Effort

Abstract: Introduction An increased perception of effort and subjective fatigue are thought to be central to decreased exercise performance observed after disrupted sleep. However, there is limited understanding of mechanisms that underpin these phenomena. We investigated the role of interleukin-6 (IL-6), the soluble IL-6 receptor, and neuroendocrine factors (cortisol, adrenaline, noradrenaline, and brain-derived neurotropic factor) in mediating these responses at rest and during exercise. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…Seventy-five publications met the inclusion criteria; however six had to be excluded because data (1) could not be extracted (or retrieved) [114][115][116]; or (2) were reported in another included publication [117][118][119]. Therefore, 69 publications remained for analysis.…”
Section: Overview Of the Included Studies And Study Qualitymentioning
confidence: 99%
“…Seventy-five publications met the inclusion criteria; however six had to be excluded because data (1) could not be extracted (or retrieved) [114][115][116]; or (2) were reported in another included publication [117][118][119]. Therefore, 69 publications remained for analysis.…”
Section: Overview Of the Included Studies And Study Qualitymentioning
confidence: 99%
“…Thus, the present study aimed to investigate whether sleep deprivation induces specific alterations of the V-wave and H-reflex responses. Because sleep deprivation increases the perceived exertion for muscle activation (Cullen, Thomas, & Wadley, 2020), we hypothesized that 24 hr of sleep deprivation would induce a reduction in maximal volitional effort and thus in V-wave amplitude recorded from the soleus muscle electromyography (EMG) during plantarflexion MVC, whereas soleus H-reflex recruitment parameters would remain essentially unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that reduced levels of available glucose (Gailliot and Baumeister, 2007 ; Cullen et al, 2020 ) and 5-ht (Zimmer et al, 2016 ) in the brain can impair cognitive control. Since glucose and 5-ht contents in blood are positively correlated with those in cerebrospinal fluid (Audhya et al, 2012 ), this study reflects changes in the central nervous system after sleep deprivation by detecting glucose and 5-ht contents in peripheral blood.…”
Section: Discussionmentioning
confidence: 99%